Pulmonary arterial pressure during rest and exercise in healthy subjects: a systematic review - Kovacs, G; Berghold, A; Scheidl, S; Olschewski, H (The European respiratory journal, 2009)
According to current guidelines, pulmonary arterial hypertension (PAH) is diagnosed when mean pulmonary arterial pressure ( P̄ pa ) exceeds 25 mmHg at rest or 30 mmHg during exercise. Issues that remain unclear are the classification of P̄ pa values <25mmHg and whether P̄ pa >30 mmHg during exercise is always pathological. We performed a comprehensive literature review and analysed all accessible data obtained by right heart catheter studies from healthy individuals to determine normal P̄ pa at rest and during exercise. Data on 1,187 individuals from 47 studies in 13 countries were included. Data were stratified for sex, age, geographical origin, body position and exercise level. P̄ pa at rest was 14.0±3.3 mmHg and this value was independent of sex and ethnicity. Resting P̄ pa was slightly influenced by posture (supine 14.0±3.3 mmHg, upright 13.6±3.1 mmHg) and age (<30 yrs: 12.8± 3.1mmHg; 30–50 yrs: 12.9±3.0 mmHg; ≥50 yrs: 14.7±4.0 mmHg). P̄ pa during exercise was dependent on exercise level and age. During mild exercise, P̄ pa was 19.4±4.8 mmHg in subjects aged <50 yrs compared with 29.4±8.4 mmHg in subjects ≥50 yrs (p<0.001). In conclusion, while P̄ pa at rest is virtually independent of age and rarely exceeds 20 mmHg, exercise P̄ pa is age-related and frequently exceeds 30 mmHg, especially in elderly individuals, which makes it difficult to define normal P̄ pa values during exercise.